The impact of the monetary policy transmission mechanism-the money supply channel on the economy - Herlina, Deswita; Suci, Stannia Cahaya; Rahman, Muhammad Rafi (Department of Accounting, Faculty of Business, Universitas PGRI Yogyakarta, 2023)
This study aims to assess the effectiveness of the monetary policy transmission mechanism on the money supply channel to the economy with the goal of prices (inflation) and income (Real GDP) from the first quarter of 2010 to the fourth quarter of 2021. The variables in this study include the BI Rate or Bank Indonesia reference interest rate, the money supply M0, the money supply M1, the money supply M2, inflation, and real GDP. The data processing phases begin with verifying data stationarity, optimum lag processing, and the Johansen co-integration test. Then this research employs an analytical method, namely the vector error correction model (VECM). The effectiveness of monetary policy transmission was analyzed using the optimal lag test. Then the impulse response and variance decomposition function to see the magnitude of the response of each variable. This study shows that the transmission of monetary policy to inflation through the money supply channel is more effective than the money supply channel to real GDP.